Understanding the Athena SWAN award scheme for gender equality as a complex social intervention in a complex system: analysis of Silver award action plans in a comparative European perspective - Evanthia Kalpazidou Schmidt; Pavel V. Ovseiko; Lorna R. Henderson; Vasiliki Kiparoglou (BMC, 2020)
Abstract Background Given the complex mix of structural, cultural and institutional factors that produce barriers for women in science, an equally complex intervention is required to understand and address them. The Athena SWAN Award Scheme for Gender Equality has become a widespread means to address barriers for women's advancement and leadership in the United Kingdom, Ireland, Australia, the United States of America and Canada, while the European Commission is exploring the introduction of a similar award scheme across Europe. Methods This study analyses the design and implementation of 16 departmental Athena SWAN Silver Action Plans in Medical Sciences at one of the world's leading universities in Oxford, United Kingdom. Data pertaining to the design and implementation of gender equality interventions were extracted from the action plans, analysed thematically, coded using categories from the 2015 Athena SWAN Charter Awards Handbook and synthesised against a typology of gender equality interventions in the European Research Area. The results were further analysed against the complexity research literature framework, where research organisations are perceived as dynamic systems that adapt, interact and co-evolve with other systems. Results Athena SWAN is a complex contextually embedded system of action planning within the context of universities. It depends on a multitude of contextual variables that relate in complex, non-linear ways and dynamically adapt to constantly moving targets and new emergent conditions. Athena SWAN Silver Action Plans conform to the key considerations of complexity - (1) multiple actions and areas of intervention with a focus on the complex system being embedded in local dynamics, (2) the non-linearity of interventions and the constantly emerging conditions, and (3) impact in terms of contribution to change, improved conditions to foster change and the increased probability that change can occur. Conclusions To enact effective sustainable structural and cultural change for gender equality, it is necessary to acknowledge and operationalise complexity as a frame of reference. Athena SWAN is the single most comprehensive and systemic gender equality scheme in Europe. It can be further strengthened by promoting the integration of sex and gender analysis in research and education. Gender equality policies in the wider European Research Area can benefit from exploring Athena SWAN's contextually embedded systemic approach to dynamic action planning and inclusive focus on all genders and categories of staff and students.